Penjabaran Peraturan Pemilihan Kepala Daerah pada Pemilihan Kepala Daerah Serentak di Masa Pandemi Covid-19 - Muhammad Yusriansyah; Riski Febria Nurita (University of Merdeka Malang, 2021)
The reason for the review, the election strategy regulated in the Government Regulation in Lieu of Law Number Long Term Year 2020 is the examination of the Act with other laws and regulations and how the results of the correlation of these laws are. As a result of this review, the author is of the opinion that, of all the guidelines related to the General Election, there have been changes in the guidelines with the expansion of welfare conventions and election guidelines during the Covid-19 pandemic as well as canceling some of the Principles in the Presidential Regulation on Elections as a mission, during the Covid-19 pandemic the mission only came to some of the gatherings of candidates and party delegates as indicated in Article 88C paragraph (1) of KPU Regulation Number 6 of 2020, and the Regulation on the Implementation of the 2020 Election only mentions the perfection of the election without knowing the current condition of Indonesia which is facing the Covid-19 pandemic